ANALISIS KOMPOSISI MEDIA TANAM ORGANIK DAN KELAYAKAN USAHA PEMBIBITAN PEPAYA - Damendra, Givana; Nofrianil; Darnetti (Green Engineering Society, 2023)
Papaya has significant business potential because demand continues to increase every year. The quality and quantity of papaya harvest really depends on quality seeds. The aim of this research is to evaluate the effect of various manures as papaya breeding media and analyze the feasibility of this business. This research was conducted at the Payakumbuh State Agricultural Polytechnic in March-May 2023 using a Completely Randomized Environmental Design. Treatment involves the use of chicken, cow and goat manure. The population used was 432 seeds with 3 treatments, each repeated 9 times, so there were 27 plots with 4 polybags per plot. Growth data were analyzed using the Anova test and the 5% DMRT test. Meanwhile, business analysis includes calculating total revenue, income, sales BEP, product BEP, price BEP, and R/C Ratio value. The research results showed that the use of various manures had a significant impact on plant growth, including plant height, leaf length and width, pH of the planting medium, and root length. However, there was no significant effect on leaf number. Business analysis revealed that treatment with Top soil, chicken manure, and husk charcoal gave optimal results with total revenue of IDR 680,000.00, income IDR 422,436.25, sales BEP IDR 126,028.96, product BEP of 31.68 polybags , the BEP price is IDR 1,515.08/polybag, and the R/C Ratio value is 2.64.